Integral Safety Needs Analysis towards Optimizing Safety Performance in Malaysian-Based Multinational Pipe Coating Industry - Dzulqarnain, Abu Bakar; Norazura, Ismail (Penerbit Universiti Malaysia Pahang, 2015)
In examining the literature on occupational safety and health management systems (OSHMS), this paper asserts that there is a need to consider the human interface when attempting to deal with a step change in safety at the workplace. The general absence of study in the integration of systems and subjective side of occupational safety has prompted this conceptual development, empirical study and theoretical reflection. The survey population was made up of on-line survey and paper questionnaire among 282 respondents. The demographics of the sample were representative of the typical mid-sized pipe-coating industry with 12% management respondent, 16% supervisory respondent, 70% shop floor respondents and the remaining 2% subcontractor respondents. There were also follow-up one-on-one interviews with 25 organization members. It can be concluded from this sample that in excess of 60% of the survey respondents expressed desire to build on the reacting, conforming and achieving stages towards achieving an integral performance level when given an option to do so. These preliminary results of initial perception survey forms the foundation the scope of study in the form of intervention and gap closure to be addressed in future researches for further promoting the integration of psychology, sociology, industrial relations and management studies to supplement existing system approaches in OSHMS.